RIFM fragrance ingredient safety assessment, 2, 2, 6-trimethyl-6-vinyltetrahydropyran, CAS registry number 7392-19-0. (15th July 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Highlights: 2, 2, 6-Trimethyl-6-vinyltetrahydropyran; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental safety. All endpoints were cleared using target data, read-across, and/or TTC.